The World Bank in India : undermining sovereignty, distorting development - Kelley, Michele; D'souza, Deepika (Orient BlackSwan, 2010)
Report of the first national Independent People's Tribunal on the Impact of the World Bank Group in India, held in New Delhi from September 21-24, 2007.